2021
DOI: 10.3390/v13061169
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antivirals in Clinical Development for Chronic Hepatitis B Infection

Abstract: Globally, chronic hepatitis B (CHB) infection is one of the leading causes of liver failure, decompensated cirrhosis, and hepatocellular carcinoma. Existing antiviral therapy can suppress viral replication but not fully eradicate the virus nor the risk of liver-related complications. Novel treatments targeting alternative steps of the viral cycle or to intensify/restore the host’s immunity are being developed. We discuss novel drugs that have already entered clinical phases of development. Agents that interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 80 publications
0
20
0
Order By: Relevance
“…In addition, the mRNA levels of TIM-3 and CTLA-4 expressions, but not PD-1 and LAG-3 mRNA, were notably increased in chronic ASCs with HBeAg-negative in comparison with HC, which were not completely consistent with previous reports ( Yu et al, 2009 ; Zhang et al, 2014 ; Cheng et al, 2021 ; Liu et al, 2021 ). The discrepancy may be associated with the number and the status of the special population who are the “inactive carrier” phase of chronic HBV infection, and these co-inhibitory receptors are also expressed in other immune cells, including CD8 + T cells, innate lymphoid cells (ILCs), and NK cells ( Kumar et al, 2009 ; Puoti, 2013 ; Riva and Chokshi, 2018 ; Tang et al, 2018 ; Mariotti et al, 2019 ; Fisicaro et al, 2020 ; Koffas et al, 2021 ; Mak et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the mRNA levels of TIM-3 and CTLA-4 expressions, but not PD-1 and LAG-3 mRNA, were notably increased in chronic ASCs with HBeAg-negative in comparison with HC, which were not completely consistent with previous reports ( Yu et al, 2009 ; Zhang et al, 2014 ; Cheng et al, 2021 ; Liu et al, 2021 ). The discrepancy may be associated with the number and the status of the special population who are the “inactive carrier” phase of chronic HBV infection, and these co-inhibitory receptors are also expressed in other immune cells, including CD8 + T cells, innate lymphoid cells (ILCs), and NK cells ( Kumar et al, 2009 ; Puoti, 2013 ; Riva and Chokshi, 2018 ; Tang et al, 2018 ; Mariotti et al, 2019 ; Fisicaro et al, 2020 ; Koffas et al, 2021 ; Mak et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results showed that serum cytokines (IL-2, IL-4, and TNF-a) had a low trend in chronic ASCs with HBeAg-negative in comparison with HC, which were partially consistent with previous reports ( Ayada et al, 2006 ; Wang X. et al, 2018 ; Zhong et al, 2021 ). These cytokines play a critical role in regulating CD4/CD8 + T cell proliferation and differentiation and the production of various specific antibodies to control persistent HBV infection ( Buschow and Jansen, 2021 ; Mak et al, 2021 ; Zhong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a further follow-up a majority of patients receiving Vebicorvir plus NUC for up to 148 weeks had <20 IU/mL of total HBV nucleic and nondetectable to very low HBeAg; also, no enrichment of CAM resistance conferring mutations was observed, likely due to the potent NUC-mediated suppression of genome replication. However, after cessation of therapy no patient cleared HBsAg and all had virological relapse [ 249 , 250 ]. Hence in favor of newer, more potent CAMs, e.g., ABI-H2158 [ 232 ] and ABI-H3733 [ 233 ], ABI-H0731 plus NUC will not go into phase 3 trials although more complex combinations are still evaluated (see Table 1 ), a common trend in the field (see Section 5.3.4 ).…”
Section: Targeting Hbv Capsid Dynamicsmentioning
confidence: 99%
“…Functional cure, defined as sustained loss of hepatitis B surface antigen (HBsAg), is a favorable endpoint in CHB due to its association with fibrosis regression [ 3 ] and reduced hepatocellular carcinoma risk [ 4 ]. It is also regarded as a clinical indicator of adequate host immune control on HBV [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple novel therapeutics, broadly classified as virus-targeting agents and immunomodulators, are being actively investigated as strategies for achieving functional cure [ 5 ]. Virus-targeting agents inhibit different steps of the HBV lifecycle and agents in development include: 1) entry inhibitors: which inhibit HBV docking and hepatocyte entry [ 6 ]; 2) polymerase inhibitors: which inhibit HBV polymerase competitively (conventional NAs) or non-competitively (novel active site polymerase inhibitor nucleotide) [ 7 ]; 3) RNA silencers: which inhibit HBV messenger RNA (mRNA) translation and viral protein production [ 8 ]; 4) capsid assembly modulators: which inhibit HBV nucleocapsid assembly and pregenomic RNA encapsidation [ 9 ]; 5) viral protein export inhibitors: which inhibit HBV antigen release from hepatocytes [ 10 , 11 ]; and 6) farnesoid X receptor (FXR) agonist: which reverses the interaction between FXR and the HBV X protein to interfere with transcription regulation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%